Novel Mutation m.10372A>G in MT-ND3 Causing Sensorimotor Axonal Polyneuropathy. (April 2021) - Bruhn, Helene; Samuelsson, Kristin; Schober, Florian A.; Engvall, Martin; Lesko, Nicole; Wibom, Rolf; Nennesmo, Inger; Calvo-Garrido, Javier; Press, Rayomand; Stranneheim, Henrik; Freyer, Christoph; Wedell, Anna; et al.
Abstract : Objective: To investigate the pathogenicity of a novel MT-ND3 mutation identified in a patient with adult-onset sensorimotor axonal polyneuropathy and report the clinical, morphologic, and biochemical findings. Methods: Clinical assessments and morphologic and biochemical investigations of skeletal muscle and cultured myoblasts from the patient were performed. Whole-genome sequencing (WGS) of DNA from skeletal muscle and Sanger sequencing of mitochondrial DNA (mtDNA) from both skeletal muscle and cultured myoblasts were performed. Heteroplasmic levels of mutated mtDNA in different tissues were quantified by last-cycle hot PCR. Results: Muscle showed ragged red fibers, paracrystalline inclusions, a significant reduction in complex I (CI) respiratory chain (RC) activity, and decreased adenosine triphosphate (ATP) production for all substrates used by CI. Sanger sequencing of DNA from skeletal muscle detected a unique previously unreported heteroplasmic mutation in mtDNA encoded MT-ND3, coding for a subunit in CI. WGS confirmed the mtDNA mutation but did not detect any other mutation explaining the disease. Cultured myoblasts, however, did not carry the mutation, and RC activity measurements in myoblasts were normal. Conclusions: We report a case with adult-onset sensorimotor axonal polyneuropathy caused by a novel mtDNA mutation in MT-ND3 . Loss of heteroplasmy in blood, cultured fibroblasts and myoblasts from the patient, and normal measurement of RC activity of the myoblasts support pathogenicity of the mutation. These findings highlight the importance of mitochondrial investigations in patients presenting with seemingly idiopathic polyneuropathy, especially if muscle also is affected.